2022
DOI: 10.3390/su141912230
|View full text |Cite
|
Sign up to set email alerts
|

Closing the Digital Gender Gap among Foreign University Students: The Challenges Ahead

Abstract: In today’s world, new and advanced forms of technology are increasingly providing great changes in universities, thus generating new possibilities and impacting pedagogy and learning methodology. Unfortunately, not all students can use these tools in the same way and with the same ability. Not only are there digital gender gaps that limit women from enjoying these learning opportunities, but there are also digital gaps between foreign and natives’ students who have been trained in these technologies in their c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…The term innovation is intrinsically interconnected to the idea of a change in educational practice in terms of novelty and transformation to improve educational processes [10]. In other words, the emphasis shifts from memorization, rote learning, teacher centeredness towards active learning, critical thinking, problem-solving, student-centeredness, self-regulation, deep learning, and collaboration.…”
Section: Educational Innovationmentioning
confidence: 99%
“…The term innovation is intrinsically interconnected to the idea of a change in educational practice in terms of novelty and transformation to improve educational processes [10]. In other words, the emphasis shifts from memorization, rote learning, teacher centeredness towards active learning, critical thinking, problem-solving, student-centeredness, self-regulation, deep learning, and collaboration.…”
Section: Educational Innovationmentioning
confidence: 99%
“…In the specific field of higher education, it has also been shown that gender inequalities in terms of access to certain university studies are positively correlated with gender gaps in ICT use. That is, among students of degrees in which there is a higher proportion of males (usually scientific‐technical degrees), gender inequalities are greater (Kerras et al., 2022). On the other hand, in the specific field of digital competence of higher education professors, this is recognised by the specialised literature as unequal between males and females.…”
Section: Literature Reviewmentioning
confidence: 99%
“…These inequalities are a reflection of the sociocultural circumstances in which professors are immersed and also cause gender inequalities in the use of ICT to be perpetuated through the students they educate (Gómez‐Trigueros & Yáñez‐de‐Aldecoa, 2021). In addition, the digital gender gap of professors is also diverse according to the area of knowledge, being greater in more technical areas (Kerras et al., 2022). For that reason, the measures that many universities have taken to try to increase the presence of women in science and technology degrees have been effective in reducing the digital gender gap (Corejova et al., 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The specialized literature reveals more explanations for gender imparity in different fields and academic disciplines [23,25,26], but empirical findings undermine their explanatory power [27]. Some of these explanations focus on microlevel factor effects, such as cognitive skills specific to each gender, perceived self-efficacy in various study fields, gender role socialization, and gender beliefs and stereotypes [13,[28][29][30]; for a review, see [31].…”
Section: Introductionmentioning
confidence: 99%